2017
DOI: 10.1093/ehjci/jex140
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic reference ranges for normal left ventricular 2D strain: results from the EACVI NORRE study

Abstract: The NORRE study provides contemporary, applicable 2D echocardiographic reference ranges for LV longitudinal, radial, and circumferential strain. Our data highlight the importance of age- and gender-specific reference values for LV strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
183
8
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 261 publications
(219 citation statements)
references
References 20 publications
19
183
8
9
Order By: Relevance
“…We found that about a third of screened patients had impaired GLS. In a cohort of 549 healthy European subjects, mean GLS was −23.3% (±3.1%) in females aged 40–60 years, compared to mean GLS in our total cohort of −18.3% (±3.1%): −17.9% (±2.9%) in anthracycline‐treated patients and −18.8% (±3.2%) in the no‐anthracycline group. It should be noted that part of this ∼5% difference may be explained by differences in the prevalence of cardiovascular risk factors associated with worse GLS.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…We found that about a third of screened patients had impaired GLS. In a cohort of 549 healthy European subjects, mean GLS was −23.3% (±3.1%) in females aged 40–60 years, compared to mean GLS in our total cohort of −18.3% (±3.1%): −17.9% (±2.9%) in anthracycline‐treated patients and −18.8% (±3.2%) in the no‐anthracycline group. It should be noted that part of this ∼5% difference may be explained by differences in the prevalence of cardiovascular risk factors associated with worse GLS.…”
Section: Discussioncontrasting
confidence: 61%
“…We performed sensitivity analyses excluding patients with a locoregional BC recurrence and/or second BC or clinical cardiovascular disease diagnosed after BC to establish their influence on outcome measures. For clinical interpretation of the data, we conducted multivariable logistic regression to study effects of treatment‐related risk factors on myocardial dysfunction prevalence, defined as a LVEF <54%, according to the range of normal LVEF values in the general female population, GLS >–17%, a cut‐off value indicative of impaired myocardial deformation, or NT‐proBNP >125 ng/L . Significance tests were two‐sided and P < 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…19,204,218 All strain values are dimensionless and are expressed as percentages. For ease of use in these recommendations, we suggest a cut-point of 16% in absolute values; [219][220][221][222] and a value below 16% (e.g. 14%) is recommended as a minor criterion.…”
Section: Minor Criterion∶ Gls < 16%mentioning
confidence: 99%
“…Although we display good inter‐observer reproducibility, it may be dependent on operator skill. However, the parameters, which we measured, have been extensively studied, and the data on their reproducibility are available in the literature …”
Section: Discussionmentioning
confidence: 99%
“…However, the parameters, which we measured, have been extensively studied, and the data on their reproducibility are available in the literature. [16][17][18]…”
Section: Study Limitationsmentioning
confidence: 99%